Atividade da NTPDase, 5 -nucleotidase, acetilcolinesterase e níveis de peroxidação lipídica em ratos expostos ao cádmio e tratados com curcumina - Costa, Pauline da (2014)
Cadmium (Cd) is one of the most toxic metals in relation to environmental contamination and human poisoning. This metal has a long biological half-life (10-30 years) and prolonged exposure to Cd has been associated with toxic effects on many organs as kidneys, liver, lungs, bone, including the brain, probably due to generation of stress oxidative. In this context, it is known that the polyphenol curcumin, natural compound derived from Curcuma longa, exerce several therapeutic functions, highlighting the great antioxidant, anti-inflammatory and neuroprotective potential. Thus, this work aims to evaluate the behavioral and memory parameters, the activity of acetylcholinesterase and ectonzimas, as well as lipid peroxidation in rats intoxicated by Cd and to determine the possible protective effect of curcumin. For this, we used 120 male Wistar rats, that received CdCl2.H2O as cadmium (Cd; 1 mg/kg) and/or curcumin (Curc, 30, 60 or 90 mg/kg) five times a week during 3 months. The animals were randomly divided into 8 groups (n = 15): (1) Saline/oil (2) Saline/Curc 30 (3) Saline/Curc 60, (4) Saline/Curc 90 (5) Cd/oil (6) Cd/Curc 30 (7) Cd/Curc 60 and (8) Cd/Curc 90. The results showed an increase in the levels of lipid peroxidation and in the AChE activity in different cerebral structures. The Cd was also increase the AChE and NTPDase (ATP and ADP as substrate) and decrease the 5 -nucleotidase activity from cerebral cortex synaptosomes. These Cd effects on central nervous system may be associated with memory deficits, evidenced by decreasing in step-down latency in the inhibitory avoidance test. Moreover, Cd also increased peripheral AChE activity of AChE (whole blood and lymphocytes) which can be associated with a pro-inflammatory state in these animals. However, Curc was effective in reducing the harmful effects of Cd decreasing lipid peroxidation and preventing increased AChE and NTPDase activities, thereby improving neurotransmission and cognitives processes, suggesting that this natural compound may be considered, after further study, an important ally in therapies against poisoning by this metal.